Differentiated Instructions in ESL and EFL Classrooms: A Systematic Literature Review - Religioni, Akifayadia; Meilinda, Calista; Alawiyah, Asri; Farrel, Luka Muhammad (STAIRS: English Language Education Journal, 2024)
Differentiated Instruction (DI) is an English teaching method that emphasizes addressing students' unique characteristics by tailoring instruction based on their interests, learning profiles, and readiness. While the concept has gained attention, a comprehensive analysis of its techniques, aspects, and impacts remains limited. This study aimed to bridge this gap by conducting content analysis on 32 articles related to DI in English classrooms. The researchers summarized, analyzed, and compared data to derive key findings. Results indicate that the study highlights DI's applicability across diverse classroom contexts and levels with diverse techniques. The reviewed articles also address the core aspects of differentiation—content, process, product, and environment—each of which involves distinct techniques, such as tiered and adjusted materials and grouping strategies. Furthermore, it identifies the positive effects of DI on students' academic performance, psychological well-being, classroom environment, and teacher practices. These findings underline the need for more holistic approaches to implementing DI and provide valuable insights for educators aiming to enhance learning outcomes through differentiated strategies.